The association between patient engagement and treatment outcome in guided internet-delivered CBT for anxiety and depression - Hammerfald, Karin; Jahren, Henrik Haaland; Solbakken, Ole André (Frontiers in Psychology, 2025)
IntroductionThe present evaluation aimed to explore patterns in routinely collected clinical data to better understand how user engagement may be associated with symptom change during guided iCBT treatment for depression and anxiety in a routine care setting. As part of ongoing quality assurance efforts, we examined whether specific engagement indicators were related to treatment outcomes. These analyses were motivated by previous findings in the literature suggesting that higher engagement may be linked to greater symptom improvement.MethodsAnonymous data of 514 patients who signed up for an internet-delivered, guided treatment program for depression or anxiety, were obtained for estimating patterns of change and the impact of predictors of change using Multilevel Modeling. Initial assessment after sign-up included various questionnaires and demographic information. Log data from user interactions with the guided iCBT programs was used to assess patient and clinician engagement. Clinical outcomes included symptoms of depression (Patient Health Questionnaire, PHQ-9) and anxiety (Generalized Anxiety Disorder-7, GAD-7).ResultsPatients started a mean of 7.14 modules, completed 64.7% of assigned modules and 62.8% of assigned activities. Patients with clinical depression or anxiety levels experienced significant changes between initial assessment and first outcome assessment as well as significant symptom reduction during treatment. Initial symptom levels and engagement persistence predicted treatment outcomes.ConclusionsThe present study replicates previous findings suggesting that safeguarding exposure to and engagement with content is significantly associated with outcome.